The Effectiveness of Liquid-Phase Microextraction of Beta-Blockers from Aqueous Matrices for Their Analysis by Chromatographic Techniques - Mihail Simion Beldean-Galea; Mihaela-Cătălina Herghelegiu; Vlad-Alexandru Pănescu; Jérôme Vial; Maria Concetta Bruzzoniti; Maria-Virginia Coman (Molecules)
Beta-blockers are pharmaceuticals used to treat cardiovascular diseases such as hypertension, angina pectoris, and arrhythmia. Due to high consumption, they are continuously released into the environment, being detected in many aqueous matrices. The aim of this research is to test the effectiveness of two green liquid-phase microextraction procedures, such as dispersive liquid–liquid microextraction (DLLME) and solidification of floating organic droplet microextraction (SFOME) for the selective extraction of eight beta-blockers (atenolol, nadolol, pindolol, acebutolol, metoprolol, bisoprolol, propranolol, and betaxolol) from aqueous matrices for their analysis by gas chromatography (GC) or liquid chromatography (LC). The influence of extraction parameters, such as the type and volume of extraction and disperser solvents, and ionic strength were studied. The developed extraction procedures provide a good enrichment factor for six compounds (61.22–243.97), good extraction recovery (53.04–92.1%), and good sample cleaning for both extraction procedures. Good limits of detection (0.13 to 0.69 µg/mL for GC and 0.07 to 0.15 µg/mL for HPLC) and limits of quantification (0.39 to 2.10 µg/mL for GC and 0.20 to 0.45 µg/mL for LC) were obtained. The developed procedures were successfully applied to the analysis of selected beta-blockers in wastewater samples, proving their applicability to the real samples.